Identification of nano clay in composite polymers. (2nd June 2014) - Tentschert, Jutta; Jungnickel, Harald; Reichardt, Philipp; Leube, Peter; Kretzschmar, Bernd; Taubert, A.; Luch, A.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; et al.
<x xml:space="preserve">Abstract</x> Industrialized food production is in urgent search for alternative packaging materials, which can serve the requirements of a globalized world in terms of longer product shelf lives, reduced freight weight to decrease transport costs, and better barrier functionality to preserve its freshness. Polymer materials containing organically modified nano clay particles as additives are one example for a new generation of packaging materials with specific barrier functionality to actually hit the market. Clay types used for these applications are aluminosilicates, which belong to the mineral group of phyllosilicates. These consist of nano‐scaled thin platelets, which are organically modified with quaternary ammonium compounds acting as spacers between the different clay layers, thereby increasing the hydrophobicity of the mineral additive. A variety of different organically modified clays are already available, and the use as additive for food packaging materials is one important application. To ensure valid risk assessments of emerging nano composite polymers used in the food packaging industry, exact analytical characterization of the organically modified clay within the polymer matrix is of paramount importance. Time‐of‐flight SIMS in combination with multivariate statistical analysis was used to differentiate modified clay reference materials from another. Time‐of‐flight SIMS spectra of a reference polymer plate, which contained one specific nano clay composite, were acquired. For each modified clay additive, a set of characteristic diagnostic ions could be identified, which then was used to successfully assign unknown clay additives to the corresponding reference material. Thus, the described methodology could be used to define and characterize nano clay within polymer matrices. Copyright © 2014 John Wiley & Sons, Ltd.